Efficacy and safety of ceftazidime–avibactam versus polymyxins in the treatment of carbapenem-resistant Enterobacteriaceae infection: a systematic review and meta-analysis - Na Chen; Ping Yang; Xiaoyang Lu; Xiaojuan Wang; Yinyan Li (BMJ Open, 2023)
Objectives Carbapenem-resistant Enterobacteriaceae is increasingly recognised as a significant public health concern. Ceftazidime-avibactam (CAZ-AVI) and polymyxins are considered as the last therapeutic options worldwide. This is the first meta-analysis of recently published data to compare the clinical efficacy and safety of CAZ-AVI with polymyxins in the treatment of carbapenem-resistant Enterobacteriaceae infections.Design Systematic review and meta-analysis.Data sources PubMed, Embase and the Cochrane Library were systematically searched, for publications in any language, from database inception to February 2023.Eligibility criteria for selecting studies Studies comparing the clinical efficacy and safety of CAZ-AVI with polymyxins were included. Mortality, clinical success, microbiological eradication and nephrotoxicity were assessed as the main outcomes.Data extraction and synthesis Literature screening, data extraction and the quality evaluation of studies were conducted by two researchers independently, with disagreements resolved by another researcher. The Newcastle–Ottawa Scale was used to assess the bias risk for the included studies. Review Manager V.5.3 was employed for the meta-analysis.Results The meta-analysis included seven retrospective and four prospective cohort studies with 1111 patients enrolled. The CAZ-AVI groups demonstrated a lower 30-day mortality (risk ratio (RR)=0.48, 95% CI of 0.37 to 0.63, I2=10%, p<0.0001) in nine studies with 766 patients; higher clinical success (RR=1.71, 95% CI 1.33 to 2.20, I2=35%, p<0.0001) in four studies with 463 patients; and lower nephrotoxicity in seven studies with 696 patients (RR=0.42, 95% CI 0.23 to 0.77, I2=35%, p<0.05). However, no significant difference in microbiological eradication rates was observed in 249 patients from two studies (RR=1.16, 95% CI 0.97 to 1.39, I2=0, p>0.05).Conclusion Available evidence suggested that CAZ-AVI treatment held a dominant position with respect to efficacy and safety compared with polymyxins in carbapenem-resistant Enterobacteriaceae infections. However, the analysis included only observational studies, and high-quality, large-scale, multicentre, double-blind randomised controlled trials are needed to confirm the advantage of CAZ-AVI.